1980
DOI: 10.1136/jnnp.43.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Late responses as aids to diagnosis in peripheral neuropathy.

Abstract: Clinical signs and symptoms of peripheral nerve dysfunction can frequently be correlated with abnormalities of conduction in groups of large motor and sensory nerve fibres'-" particularly if results from populations of patients (for example mean motor nerve conduction velocity) are contrasted with data from large numbers of normal subjects. When using standard techniques to study individual patients, however, one often finds the values for maximal motor and sensory conduction velocity to be within the normal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
7

Year Published

1981
1981
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(49 citation statements)
references
References 26 publications
4
38
0
7
Order By: Relevance
“…This, plus the observation that structural derangement of myelinated fibers usually precedes signs of clinical or electrophysiologic dysfunctions [16], ac counts for the results in our cases with chronic uremia. Moreover, we are aware that proximal nerve conduction studies [12,17], which were not done in our cases, have proved to be advantageous for screening uremic neurop athy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, plus the observation that structural derangement of myelinated fibers usually precedes signs of clinical or electrophysiologic dysfunctions [16], ac counts for the results in our cases with chronic uremia. Moreover, we are aware that proximal nerve conduction studies [12,17], which were not done in our cases, have proved to be advantageous for screening uremic neurop athy.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic studies in the past included chronic uremia cases without clinical neuropathy [1,4,5], yet few data are available regarding acute uremia [4,5], Moreover, numerous electrophysiologic studies regarding subclinical neuropathy in uremia have been reported [ 11,12,15,17,18,21 ]. In this report, it is our aim to look into the sural nerve morphology of cases with acute and chronic uremia, who had no clinical or electrophysiologic evidence of neurop athy.…”
mentioning
confidence: 99%
“…Among them are the patient's gender [48], age [49,50], measurement position [25,51], muscle tension [52], body temperature [53] and the anthropometric parameters [11,54]. The highest changes in the H-reflex parameters were observed in patients over the age of 40 years.…”
Section: Applications Of the Hoffman's Reflex Measurementmentioning
confidence: 99%
“…F-wave latencies, measured from the stimulus artifact to the beginning of the evoked potential (9) , vary by a few milli seconds from one stimulus to the next. Hence, we displayed 15 trials on a storage oscilloscope, automatically shifting successive sweeps vertically (a function provided by DANTEC F-wave analysis program).…”
Section: Methodsmentioning
confidence: 99%